Pressurised aquaria for the study of deep-water corals - B. Shillito; L. Amand; M. Zbinden; D. Barthelemy; J. Tourolle; L. Menot (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Blow Your Nose, Shrimp! Unexpectedly Dense Bacterial Communities Occur on the Antennae and Antennules of Hydrothermal Vent Shrimp - Magali Zbinden; Alison Gallet; Kamil M. Szafranski; Julia Machon; Juliette Ravaux; Nelly Léger; Sébastien Duperron (Frontiers in Marine Science, 2018)

How are microbial and detrital sources partitioned among and within gastropods species at E ast P acific R ise hydrothermal vents? - Sylvie M. Gaudron; Lise Marqué; Eric Thiébaut; Pascal Riera; Sébastien Duperron; Magali Zbinden (Marine Ecology, 2015)
For the last few decades, trophic ecology has usually been investigated by using stable isotopes. However, the isotopic signatures of potential food sources in hydrothermal vent ecosystems are often unknown and so their relative contribution to the consumers’ diet, as well as resource partitioning, are then difficult to estimate. Here, we used a recent B ayesian mixing model (stable isotope analysis in R , SIAR ) based on δ 13 C and δ 15 N to estimate the contribution of multiple food sources to the diet of eight vent gastropods that can reach high densities at hydrothermal vents ( L epetodrilus elevatus , L epetodrilus pustulosus , L epetodrilus ovalis , E ulepetopsis vitrea , C yathermia naticoides , P eltospira delicata , P eltospira operculata and R hynchopelta concentrica ). These species, known as primary consumers (mostly bacterivores and detritivores), were sampled on the S outh‐ E ast P acific R ise at 17°25′ S and the N orth‐ E ast P acific R ise at 9°50′ N and 12°50′ N. Several potential food sources were sampled according to the gastropod habitat on the chimney wall, or mussel beds (proxies of G ammaproteobacteria form I R ubis CO , G ammaproteobacteria form II R ubis CO and E psilonproteobacteria , biofilms of siboglinid and alvinellid tubes, biofilms of mussel shells and particulate organic matter). Some of these microbial and detrital sources were confirmed as present in the gut content of some small specimens by transmission electron microscopy. Distinct stable isotopic signatures of the potential food sources allowed calculation of their relative contributions to primary consumers’ diets. This revealed that gastropod species living on siboglinid or bathymodiolin habitats are usually generalists, feeding on various pools of microbial or detrital origins. For a particular habitat, sympatric gastropod species partition the food sources, thus avoiding being in competition. Only for the alvinellid habitat P eltospira spp. appeared to be more specialists as the choice of food sources is more reduced.

An improved taxonomic sampling is a necessary but not sufficient condition for resolving inter-families relationships in Caridean decapods - L. Aznar-Cormano; J. Brisset; T.-Y. Chan; L. Corbari; N. Puillandre; J. Utge; M. Zbinden; D. Zuccon; S. Samadi (Genetica, 2015)

Functional variation of sperm morphology in sticklebacks - Theo C. M. Bakker; Michael Hollmann; Marion Mehlis; Marc Zbinden (Behavioral Ecology and Sociobiology, 2014)

Dual symbiosis of the vent shrimp Rimicaris exoculata with filamentous gamma‐ and epsilonproteobacteria at four Mid‐Atlantic Ridge hydrothermal vent fields - Jillian M. Petersen; Alban Ramette; Christian Lott; Marie‐Anne Cambon‐Bonavita; Magali Zbinden; Nicole Dubilier (Environmental Microbiology, 2010)
Summary The shrimp Rimicaris exoculata from hydrothermal vents on the Mid‐Atlantic Ridge (MAR) harbours bacterial epibionts on specialized appendages and the inner surfaces of its gill chamber. Using comparative 16S rRNA sequence analysis and fluorescence in situ hybridization (FISH), we examined the R. exoculata epibiosis from four vents sites along the known distribution range of the shrimp on the MAR. Our results show that R. exoculata lives in symbiosis with two types of filamentous epibionts. One belongs to the Epsilonproteobacteria , and was previously identified as the dominant symbiont of R. exoculata . The second is a novel gammaproteobacterial symbiont that belongs to a clade consisting exclusively of sequences from epibiotic bacteria of hydrothermal vent animals, with the filamentous sulfur oxidizer Leucothrix mucor as the closest free‐living relative. Both the epsilon‐ and the gammaproteobacterial symbionts dominated the R. exoculata epibiosis at all four MAR vent sites despite striking differences between vent fluid chemistry and distances between sites of up to 8500 km, indicating that the symbiosis is highly stable and specific. Phylogenetic analyses of two mitochondrial host genes showed little to no differences between hosts from the four vent sites. In contrast, there was significant spatial structuring of both the gamma‐ and the epsilonproteobacterial symbiont populations based on their 16S rRNA gene sequences that was correlated with geographic distance along the MAR. We hypothesize that biogeography and host–symbiont selectivity play a role in structuring the epibiosis of R. exoculata .

Variability of SCCmec in the Zurich area - M. Ender; S. Burger; A. Sokoli; R. Zbinden; B. Berger-Bächi; R. Heusser; M. M. Senn; N. McCallum (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Comparative degradation rates of chitinous exoskeletons from deep-sea environments - J. Ravaux; M. Zbinden; M. F. Voss-Foucart; P. Compre; G. Goffinet; F. Gaill (Marine Biology, 2003)

Courting virtual rivals increase ejaculate size in sticklebacks ( Gasterosteus aculeatus ) - Marc Zbinden; Dominique Mazzi; Reto Knzler; Carlo R. Largiadr; Theo C. M. Bakker (Behavioral Ecology and Sociobiology, 2003)

Microsatellite markers for the three-spined stickleback (Gasterosteus aculeatus L.) and their applicability in a freshwater and an anadromous population - G. Heckel; M. Zbinden; D. Mazzi; A. Kohler; G. Reckeweg; T.C.M. Bakker; C.R. Largiadèr (Conservation Genetics, 2002)

Sperm allocation in the three‐spined stickleback - M. Zbinden; C. R. Largiadèr; T. C. M. Bakker (Journal of Fish Biology, 2001)
Male three‐spined stickleback Gasterosteus aculeatus have a fixed amount of sperm during the breeding season because spermatogenesis is inhibited at this time. A method was developed to estimate ejaculate size in situ by removing the sperm from the male's nest. The reliability of the method was tested using known numbers of sperm. In their first mating, males ejaculated 11·64 × 10 6 sperm (median), representing c. 5% of the male's sperm store (median 27·88 × 10 7 sperm). The amount of sperm in the testes was significantly reduced in males that had mated several times (median 8·09 × 10 7 ). Additionally, ejaculate size was smaller in these experienced males (median 8·79 × 10 5 ). Heavier and larger fish invested absolutely and relatively more sperm in a mating than did lighter and smaller fish. Ejaculate size did not correlate with the mass of the egg clutch.

Evaluation of commercial slides for detection of immunoglobulin G againstBartonella henselae by indirect immunofluorescence - R. Zbinden; N. Michael; M. Sekulovski; A. Graevenitz; D. Nadal (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Nephrotoxicity screening in rats; general approach and establishment of test criteria - G. Zbinden; K. Fent; M. H. Thouin (Archives of Toxicology, 1988)

Morphometric and biochemical analysis of adrenal medullary hyperplasia induced by nicotine in rats - Urs A. Boelsterli; Luis-M. Cruz-Orive; Gerhard Zbinden (Archives of Toxicology, 1984)

Significance of the LD50-test for the toxicological evaluation of chemical substances - G. Zbinden; M. Flury-Roversi (Archives of Toxicology, 1981)